2023
DOI: 10.3389/fimmu.2023.1238171
|View full text |Cite
|
Sign up to set email alerts
|

The role of ion channels in T cell function and disease

Nicholas Manolios,
John Papaemmanouil,
David J. Adams

Abstract: T lymphocytes (T cells) are an important sub-group of cells in our immune system responsible for cell-mediated adaptive responses and maintaining immune homeostasis. Abnormalities in T cell function, lead the way to the persistence of infection, impaired immunosurveillance, lack of suppression of cancer growth, and autoimmune diseases. Ion channels play a critical role in the regulation of T cell signaling and cellular function and are often overlooked and understudied. Little is known about the ion “channelom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…These peptide toxins have therapeutic potential for autoimmune diseases involving effective memory T cells activated by Kv1.3 potassium channels [25]. Eventually, ShK-186 was developed, which was 100 times more selective for Kv1.3 than for Kv1.1, Kv1.4 and Kv1.6 [61][62][63]. These ShK-like peptides have not been reported in the venom proteomes of other sea anemone species.…”
Section: Discussionmentioning
confidence: 99%
“…These peptide toxins have therapeutic potential for autoimmune diseases involving effective memory T cells activated by Kv1.3 potassium channels [25]. Eventually, ShK-186 was developed, which was 100 times more selective for Kv1.3 than for Kv1.1, Kv1.4 and Kv1.6 [61][62][63]. These ShK-like peptides have not been reported in the venom proteomes of other sea anemone species.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the BK channel is considered to have either no or little roles in the function of immune cells [29]. Notably, T and B lymphocytes do not express the BK channel [10,[30][31][32][33], and its relevance in neutrophils [34,35] and eosinophils [36] remains unclear. On the other hand, it has been reported that the BK channel may modulate macrophage phagocytosis [37].…”
Section: Introductionmentioning
confidence: 99%